2004
DOI: 10.1074/jbc.m310644200
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome c551 from Starkeya novella

Abstract: Cytochromes from the SoxAX family have a major role in thiosulfate oxidation via the thiosulfate-oxidizing multi-enzyme system (TOMES). Previously characterized SoxAX proteins from Rhodovulum sulfidophilum and Paracoccus pantotrophus contain three heme c groups, two of which are located on the SoxA subunit. In contrast, the SoxAX protein purified from Starkeya novella was found to contain only two heme groups. Mass spectrometry showed that a disulfide bond replaced the second heme group found in the diheme Sox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
27
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 49 publications
3
27
0
Order By: Relevance
“…Mass fingerprints of proteins separated on SDS-polyacrylamide gels were prepared as in Ref. 7 and analyzed using a VoyagerSTR MALDI-TOF mass spectrometer (Applied Biosystems). Electrospray mass spectrometry was performed on a Q-Star mass spectrometer (Applied Biosystems) essentially as in Ref.…”
Section: Generation Of a Site-directed Mutation Inmentioning
confidence: 99%
See 4 more Smart Citations
“…Mass fingerprints of proteins separated on SDS-polyacrylamide gels were prepared as in Ref. 7 and analyzed using a VoyagerSTR MALDI-TOF mass spectrometer (Applied Biosystems). Electrospray mass spectrometry was performed on a Q-Star mass spectrometer (Applied Biosystems) essentially as in Ref.…”
Section: Generation Of a Site-directed Mutation Inmentioning
confidence: 99%
“…It has been suggested that this modification is responsible for the multiple EPR active states observed for the SoxA active site heme (7,(12)(13)(14).…”
mentioning
confidence: 99%
See 3 more Smart Citations